PROPAGANDA POLITIK TERHADAP KOMUNIKASI BENCANA MELALUI HASHTAG DALAM PERANG SOCIAL MEDIA - Irawinne Rizky Wahyu Kusuma; Ni Putu Lindawati (Jurnal Nomosleca, 2019)
This study aims to analyze the communication linkages of disasters with political issues circulating through social media generated in the war socmed with the hashtag in the comments section of netizens. The earthquake that occurred in Bali, Lombok, and the area around West Nusa Tenggara in August 2018 became a polemic because it was juxtaposed with existing political issues. Aftershocks also occur repeatedly with a scale of 7.0 Scale Ritcher devastating most of the city of Lombok and its surroundings. With the development of time and technological advances, propaganda emerged with other forms, which were not only aimed at politics and power, propaganda also emerged with the aim of seeking profit, sympathy, and support. Propaganda can also be defined as a play of words in communication where the formulation of messages is arranged without consideration of right or wrong. Political battles do not only occur in television discussions, political campaigns, political advertisements, but also occur on social media through hashtags. This is supported by the presence of social media such as Twitter, Facebook and Instagram. Social media was targeted for netizens to conduct judgments, argumentation and political propaganda through a neutralized hashtag. This study uses qualitative research methods with analysis of discourse reconstruction and language. In principle, the hashtag analysis #2019 Change President, throws the hypothesis: 1) Will the President Change?; 2) Why Must Hashtag #2019 Change President?; 3) Is it true that a disaster occurs due to the negligence of a leader? This hypothesis is made to be used in truth in academic studies. From this study, it will be seen how social media is very influential on a condition of disaster communication links with political issues. Keywords: Political propaganda, Disaster communication, Hashtag, Media sosialDOI: https://doi.org/10.26905/nomosleca.v5i2.3227